Molecular identification of parasites in an intestinal coprolite from a mummified religious dignitary of the Piraino Mother Church crypt, Sicily. (August 2021) - Rollins, Amanda; Krupa, Krystiana; Millward, Georgia; Piombino-Mascali, Dario; Reinhard, Karl; Kaestle, Frederika
Highlights: Archaeoparasitological data can inform us of diseases in the past. Analyses of parasite remains from mummy intestinal contents are presented. This mummy was interred in the Piraino Mother Church, Sicily. He was infected with at least 2 parasitic helminths. Multiple diagnostics should be used to assess parasites in archaeological samples. Abstract: Intestinal contents were sampled from a spontaneously enhanced mummy from the Sepulcher of the Priests of the Piraino Mother Church in the Province of Messina, Sicily. This adult male mummy, Piraino 1, is an unidentified religious dignitary dating from the late-18th to mid-19th centuries. Immunological and molecular diagnostics were used to test for common and clinically significant parasites. A morphological diagnosis of Trichuris trichiura (whipworm) was confirmed genetically. A previously undetected Enterobius vermicularis (pinworm) infection was also identified genetically. These data indicate that the Piraino 1 individual was simultaneously infected with multiple intestinal parasite species indicative of poor hygiene. This study also emphasizes the importance of utilizing multiple diagnostic techniques to detect pathogens from archaeological contexts.